Diferenças sexuais no relaxamento induzido pela progesterona no leito coronariano de ratos normotensos - Giesen, Jéssyca Aparecida Soares (2019)
Progesterone seems to play a role in cardiovascular physiology, since its receptors are expressed on endothelial cells from both sexes of mammals. However, little is known about its action on coronary circulation. Thus, the purpose of this study was to investigate the acute effect of progesterone administration and the involvement of possible endothelial mediators in this action on the coronary vascular bed from normotensive rats of both sexes. We used Wistar rats of both sexes on the protocols previously approved by the Ethics Committee on Animal Use of the Federal University of Espirito Santo under protocol #64/2017. The experimental protocols were conducted by the modified Langendorff method. The vascular reactivity of the coronary vascular bed was evaluated by dose response curve of progesterone (1-50 μM, in bolus) in isolated hearts from females and males rats. Coronary perfusion pressure (CPP) was determined and the progesterone effect was assessed before and after perfusion with Nω-nitro-L-arginine methyl ester (L-NAME, 100 μM), indomethacin (2,8 μM), clotrimazole (0,75 μM), Catalase (1000 u/mL), Tiron (1 mM), apocynin (30 μM), mifepristone (1 μM) and G36 (1 μM). The analysis of nitric oxide (NO), superoxide anion (O2 ●- ) and hydrogen peroxide (H2O2) levels and were performed by DAF-2 (10 µM), DHE (5 µM) and DCF-DA (10 µM), respectively, with progesterone (50 µM) stimulation in the presence of L-NAME (300 µM), Tiron (10 µM) and catalase (1000 u/mL). The sexual difference in CPP was confirmed so that females had a higher CPP when compared with males. However, progesterone showed similar vasodilatation in both sexes. After inhibition of NO synthesis, both females and males had an increased vasodilatory response when compared to the curve performed in the absence of inhibitor. This response was confirmed with increased NO production in both sexes following stimulation with progesterone. After inhibition of prostanoids synthesis, only males had a reduced response. When we inhibited the synthesis of epoxyeicosatrienoic acids (EETs), EDHF candidate, the progesterone response was similar in both sexes. Although males showed increased production of H2O2, only females had reduced progesterone vasodilation when we inhibited this possible candidate for endothelium-derived hyperpolarizing factor (EDHF). In addition, O2 ●- appears to be involved in this response in females, since O2 ●- production was increased following stimulation with progesterone and vasodilation to progesterone was decreased both in the presence of Tiron and apocynin. After inhibition of progesterone nuclear receptors (PR), with mifepristone, the vasodilation was attenuated only in females. In contrast, after inhibition of the estrogen receptor coupled to protein G (GPER), with G36, the relaxation was abolished in both sexes. These results suggest a protective role of progesterone, which promotes relaxation in the rats coronary vascular bed of both sexes by means of sex specific endothelial mediators.